Evaluating Post-Radiotherapy Laryngeal Function with Laryngeal Videostroboscopy in Early Stage Glottic Cancer - Marciscano, Ariel E.; Charu, Vivek; Starmer, Heather M.; Best, Simon R.; Quon, Harry; Hillel, Alexander T.; Akst, Lee M.; Kiess, Ana P. (Frontiers in Oncology, 2017)
Objective Dysphonia is common among patients with early stage glottic cancer. Laryngeal videostroboscopy (LVS) has not been routinely used to assess post-radiotherapy (RT) voice changes. We hypothesized that LVS would demonstrate improvement in laryngeal function after definitive RT for early-stage glottic cancer. Study design Blinded retrospective review of perceptual voice and stroboscopic parameters for patients with early glottic cancer and controls. Setting High-volume, single-institution academic medical center. Subjects and methods Fifteen patients underwent RT for Tis-T2N0M0 glottic cancer and were evaluated with serial LVS exams pre- and post-RT. Stroboscopic assessment included six parameters: vocal fold (VF) vibration, VF mobility, erythema/edema, supraglottic compression, glottic closure, and secretions. Grade, roughness, breathiness, asthenia, strain (GRBAS) voice perceptual scale was graded in tandem with LVS score. Assessments were grouped by time interval from RT: pre-RT, 0–4, 4–12, and >12 months post-RT. Results 60 LVS exams and corresponding GRBAS assessments were reviewed. There were significant improvements in ipsilateral VF motion (P = 0.03) and vibration (P = 0.001) and significant worsening in contralateral VF motion (P < 0.001) and vibration (P = 0.008) at >12 months post-RT. Glottic closure significantly worsened, most prominent >12 months post-RT (P = 0.01). Composite GRBAS scores were significantly improved across all post-RT intervals. Conclusion LVS proved to be a robust tool for assessing pre- and post-RT laryngeal function. We observed post-RT improvement in ipsilateral VF function, a decline in contralateral VF function, and decreased glottic closure. These results demonstrate that LVS can detect meaningful changes in VF and glottic function and support its use for post-RT evaluation of glottic cancer patients.